BMI changes among U.S. Navy and Marine Corps active-duty service members during the COVID-19 pandemic, 2019-2021 - Miranda Lynn Janvrin; Amanda Banaag; Travis Landry; Carey Vincent; Tracey Pérez Koehlmoos (BMC, 2024)
Abstract Background The COVID-19 pandemic disrupted the daily life and routines of Americans across the United States (U.S.), including those of our active-duty service members (ADSMs). Limited movement orders enacted during this time to promote social distancing prohibited access to fitness and dining facilities for ADSMs. This study aims to expand on previous work identifying changes in body mass index (BMI) among U.S. Army service members by identifying changes in body mass index (BMI) among active-duty service members from both the Navy and Marine Corps during the same time period. Methods We conducted a retrospective cohort study of active-duty service members from the Navy and Marine Corps using data from the Military Health System Data Repository. BMI was calculated and categorized according to CDC guidelines both before (February 2019 - January 2020) and during the pandemic (September 2020 - June 2021). Women who were pregnant or delivered during and one year prior to the study periods were excluded. Statistical analyses included paired t-tests evaluating mean BMI, percent change, and the Stuart-Maxwell test for marginal homogeneity. Results We identified 98,330 active-duty Sailors and 55,298 active-duty Marines for inclusion in this study. During the pandemic period the percentage of Sailors with Underweight decreased by 11%, Healthy weight decreased by 11.1%, Overweight increased by 2.1%, and the percentage of Sailors with Obesity increased by 16.5%. During this same time period, Marines with Underweight decreased by 1%, Healthy weight decreased by 16%, Overweight increased by 3.0%, and Marines with Obesity increased by 51%. The largest increases in service members with overweight and obesity observed among both cohorts were among female service members, service members under age 20, and service members with a Junior Enlisted rank. Conclusions Significant increases in obesity were observed amongst active-duty United States Navy and Marine Corps service members during DoD pandemic mitigation efforts. Increased rates of obesity likely effected fitness and force readiness. Future interventions should be targeted at younger, Junior-Enlisted Marines and Sailors to promote healthy lifestyles and provide education on nutrition, appropriate exercise, sleep hygiene, and stress management.